Theology Islam [ilmu Kalam] - Ahmad Hanafi (Bulan Bintang, 1993)
ir,c.1/ast c.2,ws.c.3/ast c.4-5/ast c.6-12/ir,c.13/ir,c.14/ir,c.15/oen, c.16/ast c.17/ir,c.18/ast c.19/ir, c.20-21/en, c.22-23/en, c.24